The Development of Board Media into an Educational Game Tool with Lotto Boxes to Stimulate Fine Motor Skills in Children Aged 5-6 Years at Pertiwi Kindergarten - Khasanah, Rani Zulfia; Dea, Leli Fertiana; Utama, Ferdian (CV. Creative Tugu Pena, 2024)
Fine motor skills at the Pertiwi Kindergarten in Gajah City are still considered to be less than optimally developed compared to other levels of ability at the Pertiwi Kindergarten in Gajah City. Most young children in the 5-6 year age group have not developed optimally in terms of fine motor skills. Therefore, researchers took the initiative to develop lotto box learning media. This research is R&D research using the Borg & Gall model which consists of seven steps. The results of this research indicate that the development of lotto box media can be said to be suitable for use. The effectiveness of using lotto box media to improve the physical development aspect of fine motor skills in children aged 5-6 years is proven by the physical development of fine motor skills in children aged 5-6 years before using the lotto box media at Pertiwi Kindergarten Kota Gajah, namely students in the BB category as many as 9 children, 7 students in the MB category, while there are no BSH and BSB categories. Meanwhile, the physical development of fine motor skills in children aged 5-6 years after using the lotto box media at Pertiwi Kindergarten, Gajah City, namely that there are no more students in the BB category, 6 students in the MB category and 8 students in the BSH category. , while the BSB category already has 2 children. The physical motor skills of children aged 5-6 years at Pertiwi Kindergarten in Gajah City are starting to develop, this was shown during the research, namely that children are starting to be able to draw according to their ideas, children are able to imitate shapes, children explore with various media and activities, children are able to use writing tools. correctly, children can cut according to patterns, children are able to paste pictures correctly, and children express themselves through detailed drawing movements. Keywords: Educational Game Tool, Development Media, Children’s Education Game